2017
DOI: 10.1177/1470595817704005
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological study of time concept and management and productivity in a sub–Saharan African context

Abstract: The purpose of this article was to investigate the concept of time and its management in relation to productivity. Consequently, this work employed phenomenological psychology to unearth the experiences of employees on the concept of time management and its impact on productivity using Ghana as a study. Participants involved both local and expatriate workers sharing their experiences on the subject matter in a conversational style. Results indicated that clock time is considered a flexible resource in both soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The above findings confirm existing studies which reported that these indigenous cultures negatively affect employee efficiency (Hashimoto, 2008; Giordano and Tommasino, 2009; Van Oort and Van Nes, 2009; Yeboah-Assiamah et al , 2016; Abugre, 2017). In supporting the prior research, this study demonstrates that the indigenous cultures (gratitude, lack of punctuality, irregularity, and respect for the elderly) have distinct effects on employee efficiency and have a combined effect on employee efficiency, except that respect for the elderly will produce a positive effect.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The above findings confirm existing studies which reported that these indigenous cultures negatively affect employee efficiency (Hashimoto, 2008; Giordano and Tommasino, 2009; Van Oort and Van Nes, 2009; Yeboah-Assiamah et al , 2016; Abugre, 2017). In supporting the prior research, this study demonstrates that the indigenous cultures (gratitude, lack of punctuality, irregularity, and respect for the elderly) have distinct effects on employee efficiency and have a combined effect on employee efficiency, except that respect for the elderly will produce a positive effect.…”
Section: Resultssupporting
confidence: 91%
“…Terms like 'Ghana-man time', 'Ghanaian time', and 'African time', have been established in our cultural lexicon and emerge during funerals, festivals, traditional durbars, and other events. Despite the push for increased punctuality in the Ghanaian public sector, the ingrained nature of lateness has led to poor outcome (Abugre, 2017). This ingrained nature demonstrates that the Ghanaian culture is collectivist (Hofstede, 1980).…”
Section: B Gratitudementioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that this is not just because of attitude, but also has to do with formal institutional weaknesses relating to relaxed rules and policies on employees' time management in public sector organisations which allow employees to provide constant excuses for absenteeism (see Abugre, 2017).…”
Section: Countries Of Origin's Institutional Challenges and Weaknessesmentioning
confidence: 99%